Spatiotemporal variability in ocean-driven basal melting of cold-water cavity ice shelf in Terra Nova Bay, East Antarctica: roles of tide and cavity geometry - Kim, Taekyun; Hong, Ji-Seok; Jin, Emilia Kyung; Moon, Jae-Hong; Song, Sang-Keun; Lee, Won Sang (Frontiers in Marine Science, 2023)
Mass loss from ice shelves occurs through ocean-driven melting regulated by dynamic and thermodynamic processes in sub-ice shelf cavities. However, the understanding of these oceanic processes is quite limited because of the scant observations under ice shelves. Here, a regional coupled sea-ice/ocean model that includes physical interactions between the ocean and the ice shelf is used as an alternative tool for exploring ocean-driven melting beneath the Nansen Ice Shelf (NIS) which is a cold-water cavity ice shelf located beside Terra Nova Bay (TNB) in East Antarctica. For the first time, this study identifies the spatiotemporal variability signatures for different modes of ocean-driven melting at the base of NIS. In February (austral summer), basal melting substantially increases where the ice shelf draft is relatively small in the vicinity of the ice shelf front, contributing 78% of the total NIS melting rate. As the dominant source of NIS mass loss, this melting is driven by tide-induced turbulent mixing along the sloping ice shelf base and summer warm surface water intruding beneath and reaching the shallow parts of the ice shelf. In contrast, the NIS has relatively high basal melting rates near the grounding line in September (austral winter) primarily because of the intrusion of high-salinity shelf water produced by polynya activity in TNB that flows into the cavity beneath NIS toward the deep grounding line. Of the total melting rate of NIS in winter, 36% comes from regions near the grounding line. In addition, the contributions of tides and realistic cavity geometry to NIS basal melting are identified by conducting sensitivity experiments. Tidal effects increase the melting of NIS throughout the year, particularly contributing as much as 30% to the areas of ice draft shallower than 200 m in summer. Sensitivity results for uncertainty in cavity geometry show that spurious vertical mixing can be locally induced and enhanced by interaction between tides and the unrealistic topography, resulting in excessive basal melting near the NIS frontal band. The sensitivity experiments have shown that tides and realistic cavity geometry bring a significant improvement in the estimation of basal melt rates through a numerical model.